SISTEM INFORMASI AKUNTANSI PENJUALAN DAN PENERIMAAN KAS SEBAGAI PENGENDALIAN INTERN PADA PT GREENSPAN PACKAGING SYSTEM - Safri, Safri (Universitas Dirgantara Marsekal Suryadarma, 2016)
The purpose of this study was to determine the accounting system of sales and cash receipts on the PT Greenspan Packaging System by tracking procedures that form a network of accounting information systems cash receipts for sales, functions and related documents and accounting records are used and to be aware of the internal control of sales and cash receipts by PT Greenspan Packaging System The method used is descriptive qualitative. The tools used by the author to describe a system that runs on the PT Greenspan Packaging System is a flowchart. The results showed that the accounting information system of PT Greenspan Packaging System is good because it is run according to the procedure correctly. Internal control conducted by PT Greenspan Packaging System is good, it can be seen from the distribution of functional responsibilities, the system of authorization and recording procedures and the implementation of good practice healthy in its implementation.